The impact of Botika Binhi on essential drugs - Venida, Victor S (Archīum Ateneo, 2002)
In the Philippines, drug prices remain prohibitively high for the majority of the population in both rural and urban areas. Consequently, both government and non-government organizations sought innovative ways of streamlining and rationalizing the distribution of drugs in the country such that low-income urban and rural groups can have access to affordable and essential drugs. This article seeks to present the Botika Binhi Program as a feasible alternative to the existing freemarket system of drug distribution in the Philippines. The article first provides an overview of the pharmaceutical industry and discusses how the peculiarities of the industry lead to the marginalization of many sectors of Philippine society from adequate provision of drugs. Next, the article delves into the current patterns of consumption of drugs. In this part, the article looks into the skewed distribution and consumption of drugs as well as the prevalent pattern of drug consumption that maybe termed irrational. Afterwards, the article shows that the Botika Binhi Program, as an institutional innovation, effectively makes drugs more accessible to the marginalized sectors in Philippine society. Lastly, its projected impact on savings and consumer welfare as well as its compatibility to the industry is propounded, thus justifying the continued implementation and further expansion of the program.